Juridical Analysis of Criminal Sanctions Against Perpetrators of Money Games Using a Ponzi Scheme Model - Frizzy Rivaldy Anugrah; Rollys Suriani; Rizki Setyobowo Sangalang; Kristian Kristian (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2026)
The rapid development of financial technology has contributed to the emergence of various digital investment platforms, some of which are misused to conduct illegal activities such as Ponzi schemes. A Ponzi scheme is a fraudulent investment model that promises unusually high returns within a short period by using funds from new participants to pay earlier investors rather than generating legitimate profits. This study aims to analyze law enforcement against perpetrators of Ponzi schemes, particularly the legal implications for upline actors and the legal protection available for victims. The research employs a normative juridical method using statutory and case study approaches, with legal materials derived from legislation, legal literature, and related references. The findings indicate that Indonesia does not yet have specific regulations governing Ponzi scheme practices. Nevertheless, perpetrators may be prosecuted under Article 378 of the Criminal Code concerning fraud, Article 103 of Law Number 8 of 1995 on Capital Markets, and Article 28 paragraph (1) of Law Number 11 of 2008 on Electronic Information and Transactions as amended by Law Number 19 of 2016. Therefore, stronger and more specific regulations are needed to provide legal certainty and better protection for victims.